ACBSO: a hybrid solution for load balancing using ant colony and bird swarm optimization algorithms - Raghav, Yogita Yashveer; Vyas, Vaibhav (International journal of information technology (Singapore. Online), 2023)
In order to balance the load in cloud computing, this study suggests a hybrid technique called "ACBSO" that uses both ant-colony and bird swarm optimization techniques. Comparative analysis of the proposed hybrid algorithm has been done with Ant-colony optimization and bird swarm optimization techniques. Simulation results show that the hybrid approach outperforms both the ant-colony optimization approach and the bird swarm optimization approach. Comparison has been done based on primary factors such as makespan, throughput, fitness score, and resource consumption. To obtain the outcomes of the necessary simulations, the cloudsim simulator is employed.